Pola Asuh Orang Tua Tunggal (Single Parent) dalam Membentuk Perkembangan Kepribadian Remaja di Desa Banyutengah Panceng Gresik - Intan Faizah; Ahmad Afan Zaini (Busyro : Jurnal Dakwah dan Komunikasi Islam, 2021)
The background of the research being conducted is to find out how the parenting style given by single parent mothers to the personality development of adolescents, where as a single parent mother is certainly not easy to play a dual role in educating, and earning a living alone without a partner. The existence of factors and pressures that are felt differently between single parent mothers and one another make the parenting pattern applied also varies. The researcher used a qualitative descriptive research method with observation and interview data collection techniques, the research was conducted in Banyutengah Village, Panceng, Gresik with 3 subjects of single parent mothers and 3 subjects of teenage children. From the results obtained: one single parent mother applies authoritarian parenting, one single parent mother applies permissive parenting, and one single parent mother applies democratic parenting. Children who are raised with authoritarian parenting tend to be less confident, and closed. Children with permissive parenting tend to be less confident and have less control. Then children who are cared for with democratic parenting tend to be confident and more communicative.